Multipath effects in ultrawideband rake reception - Malik, W; Stevens, C; Edwards, D (2008)
Rake reception can improve system performance significantly in wideband multipath channels. Its practical implementation, however, becomes prohibitively expensive in channels with dense multipath, such as the ultrawideband (UWB) channel. This paper investigates the effect of various system and environment parameters on rake performance, with emphasis on the amount of multipath and channel bandwidth. The treatment includes hybrid selection/maximal-ratio combining (H-S/MRC) and unordered, partial combining rake architectures, and is based on indoor channel measurements in the FCC-allocated UWB frequency range (3.1-10.6 GHz). The diversity gain is shown to follow the law of diminishing returns with the rake complexity. It is demonstrated that the rake can extract most of the incident signal power by combining only a subset of the resolved multipath components. The required number of rake fingers increases linearly with the number of resolved paths but sublinearly with the channel bandwidth. The characterization of the interplay of bandwidth, amount of scattering and rake complexity will facilitate efficient implementation of UWB systems. © 2008 IEEE.